Feeling nature in writing: environmental education in the EFL writing course - Lestari Setyowati; Sari Karmina; Ahmad Heki Sujiatmoko; Nova Ariani (Journal on English as a Foreign Language, 2022)
Environmental degradation increases the threat to ecological disaster. Thus, environmental education is crucial for disaster mitigation. This study is intended to investigate the students’ level of environmental attitude, the students’ writing performance when writing with environmental issues, and their opinion when writing about an environmental topic. The study uses a cross-sectional design. The subjects were 23 students of the Department of English at a state university in Malang, Jawa Timur, Indonesia who joined the Essay writing course. The result shows that the students’ environmental attitude fall in the moderate category, the students’ performance in writing essays with environmental topics belongs to the ‘good’ category, and the students said that using an environmental issue raised their ecological awareness and their critical thinking skills. The result also shows that most of the students can write the introduction well, make relevant topic sentences well, give a relevant explanation well, and write a proper conclusion by using a recommendation to save and protect the environment. The study implies that environmental topics can be incorporated into language classes to sharpen language skills and to nurture the care and love of nature.